Penerapan Analisis Transaksional dalam Terapi Perkawinan Berdasarkan Pengalaman Praktek - Ahmad Gimmy Prathama Siswadi (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2012)
Transactional analysis concept is firstly introduced by Eric Berne at 60's. the books “Games People Play” and “Transactional Analysis in Psychotherapy” written by Berne, and also “I'm OK You're OK” written by Thomas Harris explain those concept obviously. Transactional analysis concept could be applied in marriage therapy. Recognition about spouse's ego state could be the early step to fix up the marriage relationship. Husband or wife could figure out the transactional situation in their relationship, whether they would like to make use of their ego state as parent, adult, or child. The relation between therapist and client, so does relation between spouses, are also the significant factor in marriage therapy. Hopefully, in-depth understanding about relationship concept in transactional analysis perspective would increase both the therapy effectiveness and the position of the clients & therapist. Example of this concept in a marriage therapy is intended to increase the understanding about how to operationalize this concept into the therapy.Keywords: transactional analysis, parent-adult-child ego state, existential position